2023
DOI: 10.3389/fvets.2023.1182930
|View full text |Cite
|
Sign up to set email alerts
|

Potential of ferritin 2 as an antigen for the development of a universal vaccine for avian mites, poultry red mites, tropical fowl mites, and northern fowl mites

Abstract: IntroductionPoultry red mites (PRMs, Dermanyssus gallinae), blood-sucking ectoparasites, are a threat to the poultry industry because of reduced production caused by infestation. In addition, tropical fowl mites (TFMs, Ornithonyssus bursa) and northern fowl mites (NFMs, Ornithonyssus sylviarum) are hematophagous, distributed in various regions, genetically and morphologically close to PRMs, and cause similar problems to the poultry industry. Vaccine approaches have been studied for PRM control, and several mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In addition, the application of homologous proteins present in different avian mites as vaccine antigens could be a valuable tool for the development of vaccines to control multiple avian mites. Recently, we reported that cysteine protease and ferritin 2 are highly conserved among avian mites, and that their application as vaccine antigens exhibits cross-protective immunity against avian mites [ 37 , 38 ]. In the present study, we characterized GSTs, which are important for the detoxification of acaricides in PRMs [ 54 ], and investigated their potential use as vaccine antigens against avian mites.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the application of homologous proteins present in different avian mites as vaccine antigens could be a valuable tool for the development of vaccines to control multiple avian mites. Recently, we reported that cysteine protease and ferritin 2 are highly conserved among avian mites, and that their application as vaccine antigens exhibits cross-protective immunity against avian mites [ 37 , 38 ]. In the present study, we characterized GSTs, which are important for the detoxification of acaricides in PRMs [ 54 ], and investigated their potential use as vaccine antigens against avian mites.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported the possible application of a single antigen as a universal vaccine for controlling avian mites [ 37 , 38 ]. This concept can encourage commercial production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations